Retene Emission from Residential Solid Fuels in China and Evaluation of Retene as a Unique Marker for Soft Wood Combustion - Shen, Guofeng (2012)
Retene (1-methyl-7-isopropylphenanthrene) is often used as a marker for softwood combustion and for polycyclic aromatic hydrocarbon (PAH) source apportionment. The emission factors of retene (EF(RET)) from 11 crop residues, 27 firewood and 5 coals were measured using traditional rural Chinese stoves. Retene was measured in combustion emissions from all of the residential fuels tested and EF(RET) varied significantly among the fuels due to the differences in fuel properties and combustion conditions. EF(RET) for pine (0.34±0.08 mg/kg) and larch (0.29±0.22 mg/kg) were significantly higher than those of other wood types, including fir and cypress (0.081±0.058 mg/kg). However, EF(RET) for crop residues varied from 0.048±0.008 to 0.37±0.14 mg/kg and were not significantly lower than those for softwood (0.074±0.026 to 0.34±0.08 mg/kg). The EF(RET) for coal were very high and ranged from 2.2±1.5 (anthracite briquette) to 187±113 mg/kg (raw bituminous chunk). EF(RET) was positively correlated with EFs of co-emitted particulate matter (EF(PM)) and phenanthrene (EF(PHE)) for crop residue and coal, but not for wood. In addition, the ratios of EF(PHE)/EF(RET) and EF(PM)/EF(RET) for coals were much lower than those for crop residues and wood. These data suggest that retene is not a unique PAH marker for softwood combustion and that coal combustion, in particular, should be taken into account when retene is used for PAH source apportionment.